Nieznane oblicza znanych leków - Gryglewski, Ryszard Jerzy (Przewodnik Lekarza/Guide for GPs, 2008)
It happens that clinicians recognize unexpectedly an unknown therapeutic property of a well known drug, and then they refer to it as a pleiotropic action of this particular drug, as long as the real mechanism of its new action is discovered. E.g. aspirin apart from its analgesic, anti-pyretic and anti-rheumatic properties, nowadays is also used at low doses as a preventive measure against myocardial infarction. Basic researchers found that in the last case aspirin acts as a selective inhibitor of cyclooxygenase 1 (COX-1) in blood platelets, and thus it prevents generation of thrombogenic and vasoconstrictor thromboxane A2 (TXA2) within the coronary circulation. Perindopril, quinapril, ramipril and other ACE inhibitors are primarily used in hypertensive patients; however, nowadays they are also recommended to patients with diabetic or atherosclerotic angiopathies. Why? Because these lipophilic ACE inhibitors act at the endothelial level as bradykinin potentiating factors (BPFs) and via B2 bradykinin receptors stimulate endothelial release of prostacyclin (PGI2), which exerts its cytoprotective action in the micro- and macrocirculation. Thiamin, known as being effective in the treatment of neuropathies, nowadays is proposed to be used in conjunction with sulphonylureas in the treatment of diabetic patients. Ascorbate appears to be a selective protector of vascular endothelium against damage caused by local generation of peroxynitrite (ONOO–). There exists nothing like a mysterious pleiotropic action of the known drugs. Simply, some of them are rich enough in their mechanisms of action as to show up their so far hidden next route of interfering with a biological system. Nowadays basic research alone is sufficient to find it out when clinicians report unknown effects of known drugs. In the second half of the 20th century there were observed remarkable examples of collaboration between clinicians and basic researchers, with Sir John Vane and Linus Pauling being excellent examples for teams of researchers. Interestingly, both of them were chemists by education and neither of them was educated in practical medicine.